(untitled) (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND: A Quasi-experimental study was undertaken to evaluate the effectiveness of Clinical Problem Based Learning (CPBL) in the care of the patient with Diabetic foot among I year BSc. Nursing students in selected colleges of Nursing in Kasaragod, Kerala.AIM: The objectives of this study were to assess the knowledge of I year B.Sc. Nursing students regarding the care of patients with Diabetic feet in experimental and control groups, evaluate the effectiveness of CPBL in the care of the patient with Diabetic feet in the experimental group, compare the post-test knowledge scores in the experimental group and control group and find out the association between the pretest level of knowledge of I year B.Sc. Nursing students regarding the care of patients with Diabetic foot with their selected variables.METHODS: The study was conducted at selected Colleges of Nursing in Kasaragod.The research approach for the study was an evaluative, pretest-posttest control group design. The sampling technique used for the study was purposive, and the research tool was the Structured Knowledge Questionnaire.RESULTS: The result of the study showed that the mean post-test knowledge score (22± 1.71) was higher than the pre-test knowledge score (12± 2.50). The calculated ‘t’ value of 13.38 was greater than the table value (t39=2.09) at a 0.05 level of significance.It was also found that there was no association between the pretest level of knowledge and selected variables.CONCLUSION: Thus, it was proved that Clinical Problem Based Learning was an effective teaching method for creating awareness regarding the care of the patient with a Diabetic foot.